Analisis Faktor - Faktor Yang Mempengaruhi Upah Tenaga Kerja Pada Karyawan Jordan Bakery Tebing Tinggi - Maheni, Masula; Jayanti, Suci Etri; Nasution, Siti Ummi Arfah (Accounting Progress, 2023)
This study aims to determine the Analysis of Factors Affecting Labor Wages for Jordan Bakery Tebing Tinggi Employees. The results of data processing use the SPSS 25 For Windows program, meaning that wages are influenced by work systems, work experience and work productivity. The results of the hypothesis test state that: Hypothesis 1 is rejected, meaning that the work system has a negative effect on work wages. Hypothesis 2 is accepted, meaning that the work experience variable has no effect on the wage variable. Hypothesis 3 is accepted, meaning that the labor productivity variable influences the work wage variable. Hypothesis 4 is rejected, from the results of multiple linear regression analysis the most dominant factor is work experience.